2020
DOI: 10.1186/s12885-020-06736-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cinnamon extract effects on clbB gene expression and biofilm formation in Escherichia coli strains isolated from colon cancer patients

Abstract: Background: Colon cancer is one of the most common malignancies and the fourth leading cause of cancerrelated mortality in the world. Colibactin, which is synthesized by the pks genomic island of E. coli interfere with the eukaryotic cell cycle. Cinnamon has an antimicrobial effect and considered as a colon cancer-preventing agent. The aim of the study was to evaluate the effects of cinnamon extract and cinnamaldehyde on clbB gene expression and biofilm formation in clinical isolates of E. coli. Methods: Thirt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…Our findings add to the efforts in identifying environmental factors that may influence colibactin expression. For example, cinnamon and cinnamaldehyde have been shown to inhibit the expression of the clbB gene among several E. coli isolates from CRC patients [ 43 ]. More recently, a new study identified compounds of tannin and quercetin from medicinal plant extracts of Terminalia catappa , Psidium guajava and Sandoricum koetjape that inhibited the growth and transcription of colibactin genes of colibactin-producing E. coli [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings add to the efforts in identifying environmental factors that may influence colibactin expression. For example, cinnamon and cinnamaldehyde have been shown to inhibit the expression of the clbB gene among several E. coli isolates from CRC patients [ 43 ]. More recently, a new study identified compounds of tannin and quercetin from medicinal plant extracts of Terminalia catappa , Psidium guajava and Sandoricum koetjape that inhibited the growth and transcription of colibactin genes of colibactin-producing E. coli [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our ndings add to the efforts in identifying environmental factors that may in uence colibactin expression. For example, cinnamon and cinnamaldehyde have been shown to inhibit the expression of the clbB gene among several E. coli isolates from CRC patients (40). More recently, a new study identi ed compounds of tannin and quercetin from medicinal plant extracts of Terminalia catappa, Psidium guajava and Sandoricum koetjape that inhibited the growth and transcription of colibactin genes of colibactin-producing E. coli (41).…”
Section: Discussionmentioning
confidence: 99%
“…The addition of natural compounds to the diet could appear to be an innovative alternative to reduce CoPEC activity. Decreased expression of clbB gene in the presence of the Sub-MIC concentrations of cinnamon essential oil and cinnamaldehyde has been observed in CoPEC isolated from CRC compared to untreated isolates [ 146 ]. Extracts of Terminalia catappa , Psidium guajava, and Sandoricum koetjape , as well as their metabolites tannin and quercetin, have been demonstrated to downregulate the expression of several clb genes in a CoPEC strain and protect eukaryotic epithelial cells from infection and DNA damage in vitro [ 147 ].…”
Section: Targeting Copec In Crc Therapymentioning
confidence: 99%